Vaccination Refusal Debate on Social Media in Turkey: A Content Analysis of the Comments on Instagram Blogs - Deniz Sümeyye Yorulmaz; Havva Karadeniz (Tehran University of Medical Sciences, 2022)
Background: This study was conducted to identify the reasons for vaccine refusal of individuals/parents by analyzing the comments on the pages screened with the keyword vaccine refusal on social media. Methods: Qualitative and quantitative methods were used in the study. Within the scope of the study, 7 pages, 216 posts and 3446 comments found with the keyword #vaccine refusal were analyzed. The comments obtained within the scope of the study were evaluated using content analysis and theme analysis methods. The study data were collected between Sep 1st and 11th, 2020. Results: The comments on vaccine refusal were found to increase in 2018 and 2019, especially in September, October, November, and December. The reasons for vaccine refusal were grouped under 2 themes as individual reasons and vaccine-related reasons as a result of the analysis of the comments. The most commonly used word in the text analysis, consisting of 10,428 words mentioned in the posts, was found to be vaccine (3.2%). Conclusion: Individuals/parents refuse vaccination for reasons such as distrust of vaccine content, disbelief in the need for vaccines, distrust of pharmaceutical companies, previous experiences, like-minded people/platforms, religious reasons, and preference for alternative health care approaches.